Tourist traffic in the Białowieża Forest in the light of research - Jalinik, Mikołaj (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Tourist traffic is a socio-economic phenomenon and it has its specific features. The increase in the pace of life has its consequences mainly in the ways of organizing free time, and it has to do with a good rest. Many definitions and classifications of tourist traffic can be found in the subject literature. The intensity of tourist traffic varies in different seasons of the year. It should be noted that in addition to the proximity of the place of residence, qualities of the natural environment have been the main motive to come to the Białowieża Forest. This has been due to such factors as the attractiveness of the area, geographic location, international events and historical conditions. Therefore, the stay in the area of the Białowieża Forest focuses mainly on its exploration, experiences, leisure and entertainment. Studies have shown that there is a clear trend towards shortening the length of stay, and a few weeks’ holiday trips to one place have a tendency virtually to disappear. At the same time, weekend trips in summer and winter are growing in popularity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 473, s. 247-256
Keywords: tourist traffic; Białowieża forest; attractions and tourist attractiveness; ruch turystyczny; Puszcza Białowieska; atrakcje i atrakcyjność turystyczna